Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1161/atvbaha.109.183707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aspirin on Clot Structure and Fibrinolysis Using a Novel In Vitro Cellular System

Abstract: Objectives-The purpose of this study was to investigate the direct effects of aspirin on fibrin structure/function. Methods and Results-Chinese Hamster Ovary cell lines stably transfected with fibrinogen were grown in the absence (0) and presence of increasing concentrations of aspirin. Fibrinogen was purified from the media using affinity chromatography, and clots were made from recombinant protein. Mean final turbidity [OD(ϮSEM)] was 0.083(Ϯ0.03), 0.093(Ϯ0.002), 0.101(Ϯ0.005), and 0.125(Ϯ0.003) in clots made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
103
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 26 publications
(22 reference statements)
5
103
0
Order By: Relevance
“…97 In an in vitro cellular model of fibrinogen acetylation by aspirin, fibrin clots were produced that were less compact, with thicker fibers. 98 Acetylation reduced clot rigidity by 30% and enhanced clot lysis, which was confirmed with fibrinogen purified from healthy individuals receiving 150 mg/day aspirin for 7 days. 98 Bjornsson et al demonstrated that in vitro acetylation of purified fibrinogen impairs the ability of fibrin to polymerize and decreases clot stability.…”
Section: Drug-related Modulation Acetylsalicylic Acid (Aspirin)mentioning
confidence: 77%
See 1 more Smart Citation
“…97 In an in vitro cellular model of fibrinogen acetylation by aspirin, fibrin clots were produced that were less compact, with thicker fibers. 98 Acetylation reduced clot rigidity by 30% and enhanced clot lysis, which was confirmed with fibrinogen purified from healthy individuals receiving 150 mg/day aspirin for 7 days. 98 Bjornsson et al demonstrated that in vitro acetylation of purified fibrinogen impairs the ability of fibrin to polymerize and decreases clot stability.…”
Section: Drug-related Modulation Acetylsalicylic Acid (Aspirin)mentioning
confidence: 77%
“…98 Acetylation reduced clot rigidity by 30% and enhanced clot lysis, which was confirmed with fibrinogen purified from healthy individuals receiving 150 mg/day aspirin for 7 days. 98 Bjornsson et al demonstrated that in vitro acetylation of purified fibrinogen impairs the ability of fibrin to polymerize and decreases clot stability. 99 An inverse correlation exists between the extent of fibrinogen acetylation and clot lysis.…”
Section: Drug-related Modulation Acetylsalicylic Acid (Aspirin)mentioning
confidence: 77%
“…Administration of low -dose aspirin was shown to be associated with improved clot properties largely through fibrinogen acetylation. 76,77 Fibrinogen is acetylated at several lysine residues, which also are involved in the FXIII -mediated cross linking of fibrin. 77 In vivo, aspirin concentration of 37.5, 320, and 640 mg/d increased K s by 44%, 31%, and 21%, respectively, and treatment with low -dose aspirin led to formation of thicker fibrin fibers with larger pores.…”
mentioning
confidence: 99%
“…Actually, clot structure is determined by several factors. 27,28 In most purified systems, as fiber size increases, pore size increases too. Fibrin networks composed of thin fiber strands have small pores and are more rigid and less permeable.…”
mentioning
confidence: 99%